Arquivo fotográfico: uma faceta do patrimônio cultural da UFSM - Pavezi, Neiva (2010)
This research aimed at promoting the diffusion of the Department of General Archives (DAG) from the Universidade Federal de Santa Maria using the elaboration of a selective photographic catalog as the strategy to meet this objective. The catalog was elaborated from the selection of ninety photographs which were representative of the UFSM University Campus construction in the period from 1960 to 1973. The theme choice reveals the importance of the modern urbanism style that characterizes the university campus and that is recorded in the selected photographs from the period that is the most representative of the campus major physical expansion. The elaboration of this research instrument implied in three different stages of study that were complementary of each other and carried out simultaneously: to determine a description instrument to the photographic archives from the analysis of the Brazilian Standard for Archival Description (Nobrade) and, the Model for Cataloging Photographic Collections (Sepiades); to collect information concerning the origin, production, accumulation and archival processing of the photographic heap; to make the catalog itself. The research was of an exploratory type, with a qualitative and descriptive approach and, aims to generate knowledge for practical application. The study carried out was exploratory, analytical and descriptive combined with the documental analysis in primary and secondary sources from the documents filed in the Institution and information collected in the literature. We also used the technique of semi-structured interviews and survey forms to make the archive diagnosis. The detailed study of Sepiades provided elements that did not recommended its application at the UFSM photographic archive; nevertheless, it supported the proposition of a set of metadata for the description of photographic archives. Besides that, the information about the photographers routine and daily life and, the construction of a photographic collection obtained from the point of view of the interviewed individuals, contributed to rescue part of the Institutional memory. Concluding, the selective photographic catalog becomes a diffusion instrument that meets the needs of the intern community as well as the needs of outside researchers who use the catalog and other documents that are made available by DAG. Furthermore, in the category of university archive, this department is, include, a repository of the Institutional administrative information, which is one of the aspects on the cultural heritage from the University, together with its architectonic heritage among others.